2022
DOI: 10.1155/2022/1902289
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Validation of Invasion-Related Molecular Subtypes and Prognostic Features for Cervical Cancer

Abstract: Background. As one of the main causes leading to female cancer deaths, cervical cancer shows malignant features of local infiltration and invasion into adjacent organs and tissues. This study was designed to categorize novel molecular subtypes according to cervical cancer invasion and screen reliable prognostic markers. Methods. Invasion-related gene sets and expression profiles of invasion-related genes were collected from the CancerSEA database and The Cancer Genome Atlas (TCGA), respectively. Samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…mTORC1 could regulate the invasion, proliferation and EMT of CESC cells through PI3K/AKT/mTORC1 pathway as one of the signaling complexes of mTOR [ 29 ]. Wang’s study identified 19 invasion-related genes and clustered the CESC into two molecular subtypes, and found TGF-beta signaling pathway was positively associated with the poor prognostic subtype [ 30 ]. In addition, our study performed survival analysis of these cancer-related pathways in CESC.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 could regulate the invasion, proliferation and EMT of CESC cells through PI3K/AKT/mTORC1 pathway as one of the signaling complexes of mTOR [ 29 ]. Wang’s study identified 19 invasion-related genes and clustered the CESC into two molecular subtypes, and found TGF-beta signaling pathway was positively associated with the poor prognostic subtype [ 30 ]. In addition, our study performed survival analysis of these cancer-related pathways in CESC.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%